Compact Microstrip Bandpass Filters Using Coupled Spiral Resonator At 2.3 Ghz - Hasan Alhawari, Adam Reda (2009)
Microstrip filters are essential components utilized in the RF/Microwave applications because of their low loss and simple structure. Moreover, it can be fabricated using simple printed circuit technology and characterize main advantages in RF/Microwave filters like high performance, light weight and low cost which the fast track of continuous evolution in wireless communication systems highly demands. This thesis presents design and development of three different microstrip bandpass filters (BPFs) for high selectivity applications. A fourth order microstrip BPF was designed using Chebychev lowpass prototype with passband ripple of 0.05 dB and bandwidth of 120 MHz, which operates at center frequency of 2.3 GHz. This filter is designed by using coupled spiral resonator, where these types of resonator structures simplify the design method for microstrip BPF and yet more efficient. This filter design is then rearranged and modified by using square spiral resonator structures and embedded-resonator topology with the same fundamental frequency to make it more compact; furthermore, it has high quality performance in terms of the frequency responses. All the microstrip BPF designs were developed and analyzed by a 3-D electromagnetic simulator. To confirm the simulation results, the three proposed filters are fabricated on R/T Duroid 5880 with dielectric constant of 2.2. The Experimental measurements are carried out using an Agilent N5230A network analyzer. The simulated and measured results are presented, compared and discussed. The analysis indicates a fairly good agreement between simulation and measurment. Finally, compact microstrip BPFs which could demonstrate high quality performance are thoroughly investigated. In this design, the minimum measured insertion loss is 2.65 dB, and the measured return loss is greater than 11 dB in the passband operating at 2.3 GHz, with a fractional bandwidth of 5.2% with two transmission zeros on both sides of the passband. The total size of this layout is 24.74 x 21.2 mm2. This new filter provides a significant size reduction of more than 30% and 18%, with respect to the conventional microstrip BPFs and the recently reported bandpass filter by Wang and others in 2008, respectively, at the same center frequency. Later, multilayer technology is used to reduce more than 25% of the filter size; which is much smaller compared to the microstrip filters using single layer structure. The new filter structure consists of four spiral resonators placed on two stacked layers where the metallic ground plane is deposited onto bottom surface of the dielectric. The measured minimum passband insertion loss is 5.2 dB with measured return loss is no more than -17 dB in the passband. The overall filter size is 380 mm2, which is approximately 10% smaller compared to the multilayer filter reported by Denidni and Djaiz in 2005. It is also reduced more than 25% and 41% compared to our proposed single layer microstrip filter and bandpass filter reported by Wang and others in 2008, respectively, at the same center frequency. It is a promising product to attract usage in modern wireless communication system applications which demand compact size bandpass filters at very low insertion loss but high selectivity, and good out-of-band rejection.